Training for confrontation to the COVID-19 in Camagüey - Jorge Luis Rivero Pérez; Tania Victoria Puerto Pérez; Lissi Maité Duarte Caballero; María Mercedes Guerra Rodríguez (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Background: In December of 2019, the authorities of China, reported a conglomerate of 27 cases of Sharp Breathing Syndrome, of unknown etiology; its expansion for the world doesn't remit and the OMS declares it pandemic March 11, for what the Cuban national system of health recommended to qualify in an early way and staggered the professionals, technicians, workers and students of the National System of Health. Objective: to describe the results of the training developed by the Department of Posgrado of the University of Medical Sciences of Camagüey for the confrontation to the COVID-19. Methods: descriptive study on training developed in threestages,from February 11 at April 30, with an universe of 71 516 professionals of the health, students of the medical sciences and other sectors. The qualitative variables were summarized by absolute numbers and percent. Results: in the first stage of the universe 88 % was qualified, in the second stage more than its population's 99 %, finally the execution stands out in the first year-old students in the careers of the medical sciences. Conclusions: the training is a continuous process, for stages and directed to specific groups, in dependence of the learning necessities that which allowed that a high number of professionals of the health, as well as of other sectors and organisms is prepared for the confrontation to this epidemic situation.